Differential Effects of Dietary Oregano Essential Oil on the Inflammation Related Gene Expression in Peripheral Blood Mononuclear Cells From Outdoor and Indoor Reared Pigs - Cappelli, Katia; Sabino, Marcella; Trabalza-Marinucci, Massimo; Acuti, Gabriele; Capomaccio, Stefano; Menghini, Luigi; Verini-Supplizi, Andrea (Frontiers in Veterinary Science, 2021)
Intensive farming systems represent a stressful environment for pigs and negatively influence neuroendocrine functions, behavior and performance. Outdoor farming is an alternative option, which is thought to imply several beneficial effects for the animal. Dietary essential oils are known to be an innovative strategy to improve swine health and performance and oregano essential oil possesses beneficial effects due to its antimicrobial, anti-fungal, and antioxidant properties. We tested the effect of dietary oregano essential oil (ORE) on peripheral blood mononuclear cells in 36 growing pigs, either reared under indoor or outdoor conditions. RT-qPCR assay was used to evaluate the effect of diet (control vs. ORE) and time of sampling (T1 - 120 d vs. T2 - 190 d) on the expression of inflammatory and immune-related genes (TNF-α, IL-1β, IL8, IL18, IL10, IL1RN, STAT3, HSP90, ICAM-1, NF-κB-1). Under outdoor condition, the majority of transcripts were up-regulated (P < 0.05) assuming a general inflammatory status (TNF-α, HSP90, NF-κB-1, IL1β and STAT3). However, an interaction between diet and farming system was observed: HSP90, NF-κB-1 and STAT3 were down regulated (P < 0.05) in the outdoor reared pigs when fed the ORE diet. Our study showed that bioactive compounds of oregano essential oil exert their activity especially when the animals are exposed to stressful stimuli. Dietary oregano can be an acceptable strategy to help pigs tolerate the stress related to harsh, outdoor, rearing conditions.